(untitled) (Bangladesh Journal of Medical Education, 2018)
Proper doctor-patient communication produces therapeutic benefit on the patient. The arts and tips of communication skill can change the feelings of a patient forever. Good communication skill should have verbal, non-verbal and para-verbal components. Unfortunately, many postgraduate doctors of our country cannot satisfy the demand of their patients due to lack of training on communication skills. In this paper, a model for communication skill training has been proposed for newly graduated doctors which includes formal lecture, video demonstration, role play and evaluation by creating different scenarios. The selected time for communication skill training would be the time gap between publication of result of final professional MBBS and starting the internship training. With increasing demand of creating more communicative physicians, implementation and further recommendations on communication skill training for new graduates are encouraged. Bangladesh Journal of Medical Education Vol.9(2) 2018: 32-36